2020
DOI: 10.1002/onco.13633
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Analogs for Pancreatic Neuroendocrine Tumors: Any Benefit When Ki-67 Is ≥10%?

Abstract: Background Long‐acting somatostatin analogs (SSAs) are the primary first‐line treatment of well‐differentiated advanced gastroenteropancreatic neuroendocrine tumors (NETs), but data about their efficacy in pancreatic NETs (panNETs) with Ki‐67 ≥10% are still limited. Materials and Methods To assess the clinical outcomes of advanced, nonfunctioning, well‐differentiated panNETs with Ki‐67 ≥10% receiving first‐line long‐acting SSAs in a real‐world setting, we carried out a retrospective, multicenter study includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
0
19
1
Order By: Relevance
“…They did not note any statistically significant difference between octreotide and lanretotide on PFS. Lastly, they demonstrated that SSA exerted antiproliferative activity against intermediate and high grade pNETs, with both octreotide LAR and Lanreotide being associated with a median time to next treatment of 14.2 month and a median PFS of 11.9 months [ 54 ]. Although mild adverse effects, such as hyperglycemia and pancreatic enzyme insufficiency, could have been associated with SSA therapy, our patient responded very well with resolution of diarrhea, complete remission of the NME and significant metabolic improvement.…”
Section: Discussionmentioning
confidence: 99%
“…They did not note any statistically significant difference between octreotide and lanretotide on PFS. Lastly, they demonstrated that SSA exerted antiproliferative activity against intermediate and high grade pNETs, with both octreotide LAR and Lanreotide being associated with a median time to next treatment of 14.2 month and a median PFS of 11.9 months [ 54 ]. Although mild adverse effects, such as hyperglycemia and pancreatic enzyme insufficiency, could have been associated with SSA therapy, our patient responded very well with resolution of diarrhea, complete remission of the NME and significant metabolic improvement.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was only limited biological tumor evidence and rationale for this threshold. Interestingly, a recent study demonstrated the antiproliferative efficacy of SSA, particularly in NET G2 Ki-67 >10%, with a median PFS of 12.4 months [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A subset of GEP-NET patients present with extensive tumor bulk or high proliferative rate (Ki-67 index of 10–55%). In these cases, treatment with octreotide LAR or lanreotide has questionable antiproliferative effects [ 71 ]. Given its ORR of 39%, which increases to 55% in panNETs [ 29 ], 177 Lu-DOTATATE can be considered as first-line therapy if response is clinically necessitated [ 72 ].…”
Section: Patient Selectionmentioning
confidence: 99%